Pengembangan Infrastruktur Rumah Susun Berbasis Prinsip-Prinsip Pusat Transit Skala Kecamatan di Kota Makassar - Muhammad Firdaus; Shirly Wunas; Mimi Arifin (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
Makassar City has 2 cluster of flats located in 2 different locations and managed by the local goverment. One of them is located in the coastal region which is the case of this study. Furthermore, the flats are located in densely settlement areas with inadequate social and economic facilities where conduce the local resident taking long distance by using vehicles to fulfill their necessity. And inefficiencies costs, time and traffic. The purpose of this research are to analyze the social-economic facilities of resident who stay in the flat, analyzing the movements of the resident in reaching out the social-economic facilities, and also to arrange the foundation of Transit-Oriented Development (TOD) that are good for transportation and tight up the various functions of land within an area. The data used are derived from the results of interviews with 206 respondents, which are determined based on probability sampling, which is simple random. The research methodology used is a descriptive qualitative method, spatial analysis, and comparative. The results of the research show that the availability of social-economic facilities is appropriate with the needs of the residents. The movement of the resident in the flat is still dominant by using their own vehicles in reaching social and economic facilities (±500m-±1000m). The development direction based on the principle of Transit Oriented Development (TOD) such as to tight up and build a variety of social and economic necessity in an area (mix use), and also to build up a safe and comfortable pedestrian and cycling track in that area.